Design and Experimental Analysis of Ventilated Walls and "Ice House" Roofs Applications in Warm Climates - SHIH, Jason C; FAIREY, Philip W.; SHIH, Jeffrey A. (ARCC Conference Repository, 2019)
This paper contains the findings of experimental research conducted to determine the effectiveness of ventilated walls and "ice house" roof applications in hot-humid climates. Ventilated wall and "ice house" roof is the type of construction which consists of interposing an additional wall or roof skin between the standard building envelope and the exterior environment. The new skin is separated from the building envelope by an air space, which is usually vented to the ambient environment. The primary objective of such construction is to eliminate or drastically reduce the effects of solar loading on the building envelope. The information presented in this paper can enable the designer to have a better understanding of how buildings might function at various times of the day and the season. Recommendations on applications of new buildings and retrofit of existing structures are presented here as well.